Pengaruh Digital Marketing terhadap Usaha Mikro Kecil Menengah - Phoebe, Jane; Rivan Hadiwinoto, Roberto Amadeus; Marcellina, Rudya; Natanael, Wilbert; Aly Alfarisi, Naufal; Kho, Shiana; Libertus, Samuel; Roberto Justin, Theodore; Arrina Rachman, Rathria (Journal Pemberdayaan Masyarakat Indonesia, 2022)
The purpose of this paper is to describe the effects of digital marketing strategies that the group has used to assist Mr. Chandra, the owner of Pempek Cek Ya with growing his online presence in the social media space. According to the interview that we have done, there is a large amount of room for improvement in the digital marketing side of the business as we noticed that the business has not yet utilized their social media, advertisements, sales promotion, nor marketing mix to its maximum potential. This results in the business not having a good amount of brand awareness in its market. We have used a few digital marketing strategies which have successfully helped the business to increase their online presence, which we will discuss in this paper. Through this paper, we hope other Micro, Small and Medium Enterprises (MSME) may be able to increase their marketing efforts, and use the strategies that we have used to have a much better and improved brand awareness in their own markets.